UiTMLaw wins two awards during the MeTIC Award 12/2023 - UiTM, Faculty of Law (Faculty of Law, 2023)
UiTMILaw won two awards during the IMeTIC Award in 12/2023. The awards received were the third place for the Best Industry Collaboration Award category for the UiTMLaw industry. Alumni Mentorship Programme "Inspiring Future Leaders" and second place for the best KTIP Project Award category for the Focus Group Discussion Orang Asli Pos Pulat and Pos TohoI program, Nenggiri, Kelantan. These awards were given during the Deputy Vice-Chancellor's (Industry Community and Alumni Network) (MeTIC) Meeting 12/12/2023 held at Hotel Impiana, lpoh, Perak. UiTMILaw Industry-Alumni Mentorship Programme Inspiring Future Leaders" is one of the initiatives of the Faculty of Law to provide exposure to real-life work experience through the appointment of a mentor who is responsible for guiding students known as mentee. The progamme was conducted in 4 series and will continue following the overwhelming response. from mentors and mentees. The IFocus Group Discussion Program Orang Asli Pos Pulat and Pos Tohol, Nenggiri, Kelantan is a discussion program through knowledge transfer program. made by a team of UiTM and UKM experts with the indigenous people of Pos Pulat and Pos Tohol on the rights of indigenous people to land in terms of land law and the federal.